The business of venture capital : the art of raising a fund, structuring investments, portfolio management, and exits - Ramsinghani, Mahendra (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
"This book addresses the entire spectrum of investing and is focused toward seed and early-stage venture investments. Raising a fund, sourcing and investing, and exits are interlinked aspects of the VC business. After reading the insights of various practitioners, aspirants will be able to appreciate the intricacies of the venture capital business and have a stronger understanding of the basics"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Venture capital